Acute Neurologic Complications During Extracorporeal Membrane Oxygenation: A Systematic Review. Issue 9 (September 2018) - Sutter, Raoul; Tisljar, Kai; Marsch, Stephan
Abstract : Objectives: We determine the frequency, risk factors, and mortality of neurologic complications in adults on extracorporeal membrane oxygenation and propose an algorithm for preventive strategies. Data Sources: PubMed, Embase, and Cochrane databases. Study Selection: Screening was performed using predefined search terms to identify cohort studies reporting neurologic complications in adults during extracorporeal membrane oxygenation from 1990 to 2017. Data Extraction: The final reference list was generated on the basis of relevance to the discussed topics. Quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation classification of evidence scheme. Data Synthesis: In 44 studies, the median frequency of acute neurologic complications is 13% (1–78%; 5% intracranial hemorrhages, 5% ischemic strokes, 2% seizures). Neurologic complications are reported more frequently with venoarterial extracorporeal membrane oxygenation compared with venovenous extracorporeal membrane oxygenation (14 vs eight studies) with a median proportion of complications of 15% (6–33%; 95% CI, 8–19) for venoarterial extracorporeal membrane oxygenation. Median in-hospital mortality is higher with neurologic complications (83%; interquartile range, 54–100% vs 42%; interquartile range, 24–55% without neurologic complications; p < 0.001). Median mortality is 96% for hemorrhages, 84% for ischemic strokes 84%, and 40% for seizures. Risk factors are age, preextracorporeal membrane oxygenation cardiac arrest, hypoglycemia, and administration of inotropes. Hemorrhages are associated with female gender, duration of ventilation and extracorporeal membrane oxygenation, decreased serum fibrinogen, heparin, serum creatinine greater than 2.6 mg/dL, hemodialysis, and thrombocytopenia. Increased odds for ischemic stroke is seen with a preextracorporeal membrane oxygenation serum lactate greater than 10 mmol/L. No studies report daily coagulation monitoring and neurologic assessments, and quality of evidence was low to very low. Conclusions: Neurologic complications are reported frequently and with high occurrence rate, especially with venoarterial extracorporeal membrane oxygenation, and associated with high mortality calling for daily weaning from sedation and neuromuscular blockers for neurologic assessment and coagulation monitoring. The low quality of evidence indicates the need for higher quality studies in this context. Abstract : Supplemental Digital Content is available in the text.